What Does Writing a Research Thesis in Psychology Mean in Peru? - León, Federico R. (2016)
In compliance with the recent Peruvian University Law, students who apply for a professional license may opt to write a thesis, but the requirement of a thesis is mandatory for a master´s or a doctorate degree to be granted. However, many academics seem confused on the nature of the thesis itself. In this paper, firstly, I contrast contribution to knowledge with student learning and qualification of competences; secondly, I review reasonable demands for each degree level; thirdly, show why present theses still conform to a bureaucratic and encyclopedic style which slows the process of conversion into a scientific article; finally, I discuss the role of the supervisor, and point out some of the risks of authoritarianism due to topic selection and acceptability.